Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Let f (x) = 3x + 1 and let g(x) = x - 1. Find (fog) (5)
0 0
O 15
O 4
O 7


Sagot :

Answer:

13

Step-by-step explanation:

(fog)=3(x-1)+1

ie puting the function of g in f

so (fog)= 3x-3 + 1= 3x-2

finding fog

(fog)(5)= 3(5)-2

ie sub stitute 5 in x

(fog)(5)=15-2=13